Jacqueline Bouvier Kennedy Onassis : the untold story - Leaming, Barbara (St. Martin's Press, 2014)
A book that explores the seemingly magical world of Jackie Onassis' youth, her fairy-tale marriage to a wealthy and handsome senator and presidential candidate and her astonishing transformation into a deft political wife and unique first lady also explores what the author asserts was Jackie's 31-year struggle with PTSD after the assassination of her husband, John F. Kennedy.